2014
DOI: 10.1089/mdr.2013.0141
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of oqxAB in Escherichia coli Isolates from Domestic and Wild Lagomorphs in Italy

Abstract: This study aimed to identify and characterize class 1 and 2 integrons and plasmid-mediated quinolones resistance (PMQR) genes in a collection of 113 multidrug resistance (MDR) Escherichia coli isolated from farm and wild lagomorphs between 2006 and 2008 in Northern Italy. Strains were examined for antimicrobial susceptibility by agar disk diffusion method and E-test for colistin (COL); integrons and gene cassettes content by real-time polymerase chain reaction (PCR) and DNA sequencing; PMQR genes by PCR and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
5
17
1
1
Order By: Relevance
“…Others have reported a similar prevalence of colistin resistance in E. coli in wildlife (e.g. European herring gulls, lagomorphs) that is also independent of mcr-1 (Dotto et al, 2014; Ruzauskas & Vaskeviciute, 2016). With a renewed interest in colistin as a last resort antimicrobial drug and the introduction of additional testing/screening, perhaps the collective findings represent a case of background antimicrobial resistance that is naturally occurring in the environment and in wildlife, and which is unrelated to direct or indirect anthropogenic sources.…”
Section: Colistin Resistance In E Colimentioning
confidence: 82%
“…Others have reported a similar prevalence of colistin resistance in E. coli in wildlife (e.g. European herring gulls, lagomorphs) that is also independent of mcr-1 (Dotto et al, 2014; Ruzauskas & Vaskeviciute, 2016). With a renewed interest in colistin as a last resort antimicrobial drug and the introduction of additional testing/screening, perhaps the collective findings represent a case of background antimicrobial resistance that is naturally occurring in the environment and in wildlife, and which is unrelated to direct or indirect anthropogenic sources.…”
Section: Colistin Resistance In E Colimentioning
confidence: 82%
“…Dependent on the host TolC protein, OqxAB has a wide substrate specificity, making E. coli also more resistant to fluoroquinolones, nalidixic acid, chloramphenicol, trimethoprim, benzalkonium chloride, and SDS (709). The oqxAB genes have since increasingly been found on R plasmids from E. coli (710)(711)(712)(713)(714) and several other species of Enterobacteriaceae, such as Salmonella and K. pneumoniae (235,236,303,715). The coexistence of the oqxAB and floR or CTX-M gene on the same plasmids was also observed (713,715).…”
Section: Drug Efflux Genes On Plasmidsmentioning
confidence: 99%
“…In addition, it has been reported that colistin-resistant E. coli were isolated from wild rabbits ( Oryctolagus cuniculus ) and wild hares ( Lepus europaeus ) that have not been previously treated with colistin (Dotto et al, 2014). Consequently, wildlife may represent another potential reservoir of colistin resistance bacteria in the environment that could contaminate humans through contaminated food and water or by direct human and animal contact (Gelbrand et al, 2015).…”
Section: One Health Perspectivesmentioning
confidence: 99%